Is There a Secret Ballot? Ballot Secrecy Perceptions and Their Implications for Voting Behaviour. Issue 1 (3rd July 2012) - Gerber, Alan S.; Huber, Gregory A.; Doherty, David; Dowling, Conor M.
Abstract : Do people believe the votes they cast are truly secret? Novel items added to a nationally representative survey show that 25 per cent of respondents report not believing their ballot choices are kept secret and over 70 per cent report sharing their vote choices with others. These findings suggest that standard models of candidate choice should account for the potential effects of doubts about ballot secrecy. Consistent with this view, regression analysis shows that social forces appear to have a greater effect on vote choices among people who doubt the formal secrecy of the ballot. This analysis supports the broader claim that the intended benefits of institutional rules may not be realized if people's perceptions of these rules differ from their formal characteristics.